2013
DOI: 10.1021/ja403008j
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preparation of a Core–Shell Metal–Organic Framework for Selective CO2 Capture

Abstract: The design of a core-shell metal-organic framework comprising a porous bio-MOF-11/14 mixed core and a less porous bio-MOF-14 shell is reported. The growth of the MOF shell was directly observed and supported by SEM and PXRD. The resulting core-shell material exhibits 30% higher CO2 uptake than bio-MOF-14 and low N2 uptake in comparison to the core. When the core-shell architecture is destroyed by fracturing the crystallites via grinding, the amount of N2 adsorbed doubles but the CO2 adsorption capacity remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
175
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(178 citation statements)
references
References 29 publications
3
175
0
Order By: Relevance
“…This further allowed for growth of the bio-MOF-14 shell and, after repeating the procedure three times, afforded II@bio-MOF-14, where II denotes the core C20.60C50.57 (with C2: acetate and C5: valerate). [190] The hybrid material adsorbed 30% more CO2 than bio-MOF-14 (44.8 cm 3 /g) with a much lower N2 uptake at 77 K, suggesting that the shell efficiently prevents any significant N2 uptake by the core. [190] To confirm this, the material was ground, and found that a significantly higher amount of N2 was adsorbed at 77 K (108 cm 3 /g compared to 54 cm 3 /g), thus it is likely that the N2 molecules have to pass through the bio-MOF-14 shell to enter the porous core.…”
Section: Co2 Capturementioning
confidence: 95%
See 2 more Smart Citations
“…This further allowed for growth of the bio-MOF-14 shell and, after repeating the procedure three times, afforded II@bio-MOF-14, where II denotes the core C20.60C50.57 (with C2: acetate and C5: valerate). [190] The hybrid material adsorbed 30% more CO2 than bio-MOF-14 (44.8 cm 3 /g) with a much lower N2 uptake at 77 K, suggesting that the shell efficiently prevents any significant N2 uptake by the core. [190] To confirm this, the material was ground, and found that a significantly higher amount of N2 was adsorbed at 77 K (108 cm 3 /g compared to 54 cm 3 /g), thus it is likely that the N2 molecules have to pass through the bio-MOF-14 shell to enter the porous core.…”
Section: Co2 Capturementioning
confidence: 95%
“…[190] The hybrid material adsorbed 30% more CO2 than bio-MOF-14 (44.8 cm 3 /g) with a much lower N2 uptake at 77 K, suggesting that the shell efficiently prevents any significant N2 uptake by the core. [190] To confirm this, the material was ground, and found that a significantly higher amount of N2 was adsorbed at 77 K (108 cm 3 /g compared to 54 cm 3 /g), thus it is likely that the N2 molecules have to pass through the bio-MOF-14 shell to enter the porous core. [190] In addition, the encapsulation of guanidium (GND + ), aminoguanidinium (AmGND + ) and diaminoguanidinium (DiAmGND + ) within bio-MOF-1 was also studied and determined how this can impact on the CO2 adsorption properties, as well as their capacities and isosteric heat of adsorption.…”
Section: Co2 Capturementioning
confidence: 95%
See 1 more Smart Citation
“…There are examples of full ligand exchange 13 and the synthesis of core−shell MOFs. 14 The second strategy looks more promising for compact structures as compound 2. The Gly-Asp dipeptide potentiates the generation of 3D frameworks through the extra coordination opportunity provided by the Asp side chain.…”
Section: Resultsmentioning
confidence: 99%
“…This way, the overall material properties can be enhanced by combining different functionalities in the core and shell layers 11. For example, the integration of a shell crystal with selective gas sorption with a core crystal with high pore volume makes it possible to combine gas selectivity with high gas storage capacity 12. Also, core–shell nanostructures with an inner core nanoparticle encapsulated by a porous shell have been widely used for heterogeneous catalysis, where the shell material can ensure the accessibility of reactant molecules to the active metal and also improve the selectivity and stability of the catalyst 13.…”
mentioning
confidence: 99%